Qualitative and Quantitative Characteristics Analysis in Texel Crossed , Dorper and Fat Tailed Sheep - Sucik Maylinda; VM. A. Nurgiartingsih; N. Isnaeni; S. B. Siswijono; A. Furqon (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The aims of present study was to evaluate the qualitative and quantitative characteristics of imported sheep such as Texel crossed and Dorper sheep, compared with local sheep (Fat Tail Sheep/FTS) in almost the same region, namely Pujon and Karangkates. This research was a field research with case study methods and research materials as many as 39 for Texel crossed sheep, 19 for Dorper sheep and 37 for FTS. The age of the sheep ranges from 1.5 to 3 years (some have their first calf). Qualitative data were analyzed by Population Genetics Analysis and quantitative data were analyzed by One-Way Design Anova using Minitab software version 13. The results showed that: (1) Qualitative traits in Texel crossed , Dorper and FTS sheep showed that some traits underwent fixation where one of the traits was fixed. One allele in Texel crossed and Dorper sheep has disappeared and no longer exist in its origin place such as horned and hornless traits, white body color and black head, erect ears, while in FTS sheep it is still polymorphic, especially in the hornless and drooping ears in FTS. The white color on the FTS seems to have been fixed, because the dominant gene frequency/ p = 1 and the recessive gene frequency/ q = 0. (2) The quantitative traits such as body weight, in which the body weights of the Texel crossed , Dorper and FTS breed were different in the study, and the Dorper sheep the highest body weights, while the body weights of Texel crossed and FTS sheep were almost the same. Dorper sheep had the highest head index, and Texel crossed sheep and FTS sheep had the same head index. It was concluded that Texel crossed and Dorper sheep had many fixed qualitative characteristics such as horns, erect and drooping ears, white body color and black head in FTS sheep were quite polymorphic in horns and erect and drooping ears. The best growth of Dorper sheep because Dorper sheep was originated from a crossing between Dorset and Black Persian sheep.